Pengaruh Faktor Komunikasi, SDM, Disposisi Dan Struktur Birokrasi Dalam CDAKB Serta Dampaknya Terhadap Kinerja Usaha PAK - Astuti, Dewi; Aritonang, MGS; Fuad Afdhal, Ahmad (Journal Syifa Sciences and Clinical Research (JSSCR), 2024)
Medical devices are instruments, apparatus, machines and implants that do not contain drugs that are used to prevent, diagnose, cure and relieve disease, treat sick people, restore human health and form the structure and improve body function. In the Minister of Health Regulation Number 4 of 2014 article 2 paragraph (1) it is stated that "Every medical equipment distributor and medical equipment distribution branch in carrying out distribution activities is obliged to implement Good Medical Device Distribution Methods". The aim of this research is to determine the influence of communication, resource, disposition and structural factors on how to distribute medical devices well and their impact on the business performance of medical equipment distributors. The research method used is descriptive research with a quantitative approach. Data was obtained through interviews and filling out questionnaires with 92 respondents from medical equipment distribution businesses. The results of the research show that the factors of communication, resources, disposition and bureaucratic structure have a positive influence on the implementation of Good Medical Device Distribution Methods, the implementation of Good Medical Device Distribution Methods has a positive influence on the business performance of Medical Equipment Distributors and the communication, resources, disposition and The bureaucratic structure has a positive influence on the business performance of Medical Equipment Distributors. Based on the research results, it can be concluded that the variables of communication, resources, disposition and bureaucratic structure have a positive effect on the implementation of CDAKB and PAK. The variables of CDAKB implementation, communication, resources, disposition and bureaucratic structure also have a positive influence on PAK's business performance.